Gene expression comparison of biopsies from Duchenne muscular dystrophy (DMD) and normal skeletal muscle - Haslett, J. N.; Sanoudou, D.; Kho, A. T.; Bennett, R. R.; Greenberg, S. A.; Kohane, I. S.; Beggs, A. H.; Kunkel, L. M. (Proc Natl Acad Sci U S AProc Natl Acad Sci U S AProc Natl Acad Sci U S A, 2002)
The primary cause of Duchenne muscular dystrophy (DMD) is a mutation in the dystrophin gene leading to the absence of the corresponding RNA transcript and protein. Absence of dystrophin leads to disruption of the dystrophin-associated protein complex and substantial changes in skeletal muscle pathology. Although the histological pathology of dystrophic tissue has been well documented, the underlying molecular pathways remain poorly understood. To examine the pathogenic pathways and identify new or modifying factors involved in muscular dystrophy, expression microarrays were used to compare individual gene expression profiles of skeletal muscle biopsies from 12 DMD patients and 12 unaffected control patients. Two separate statistical analysis methods were used to interpret the resulting data: t test analysis to determine the statistical significance of differential expression and geometric fold change analysis to determine the extent of differential expression. These analyses identified 105 genes that differ significantly in expression level between unaffected and DMD muscle. Many of the differentially expressed genes reflect changes in histological pathology. For instance, immune response signals and extracellular matrix genes are overexpressed in DMD muscle, an indication of the infiltration of inflammatory cells and connective tissue. Significantly more genes are overexpressed than are underexpressed in dystrophic muscle, with dystrophin underexpressed, whereas other genes encoding muscle structure and regeneration processes are overexpressed, reflecting the regenerative nature of the disease.
Keywords: *Gene Expression Regulation; *Reverse Transcriptase Polymerase Chain Reaction; Adult; Child; Child, Preschool; Female; Humans; Male; Muscle Proteins/*genetics; Muscle, Skeletal/cytology/*pathology/physiology/physiopathology; Muscular Dystrophy, Duchenne/*genetics/*pathology; Oligonucleotide Array Sequence Analysis; probability; Reference Values; Regeneration; Reproducibility of Results; Signal Transduction/genetics